Evaluating the Performance of Small Wastewater Treatment Plants - Engstler, Eva; Kerschbaumer, David J.; Langergraber, Guenter (Frontiers in Environmental Science, 2022)
An evaluation of the treatment performance of small wastewater treatment plants (WWTPs) with the capacity of ≤ 50 PE (population equivalent) was carried out using data collected in external monitoring reports, taking Upper Austria as an example. External monitoring data for 2009 - 2018 were available for this analysis. About 2'500 small WWTPs are in operation in Upper Austria. The main technologies implemented include about 870 Sequencing Batch Reactor (SBR) plants, 630 conventional activated sludge (CAS) plants and 535 vertical flow (VF) wetlands. The data set for the present evaluation comprises a total of approx. 14'000 external monitoring reports from approx. 2'000 small WWTPs. This paper presents the results of this evaluation. The evaluation showed that all technologies meet the legal requirements regarding BOD5, COD and NH4-N effluent concentrations. However, for small WWTPs with a polishing stage consisting of a VF wetland, the median values of the effluent concentrations and the limit value exceedances are significantly lower. There is no evidence of a significant deterioration in treatment performance with the age of the plant for any technology. However, for all technical WWTPs such as SBR and CAS plants, a greater fluctuation of the measured values (i.e. the median values of the effluent concentrations) can be observed when the plant is longer in operation. Compared to technical WWTPs, this fluctuation is significantly smaller in VF wetlands.